2020
DOI: 10.1177/1350650119899213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation and experimental study on the lubrication of graphene additive films

Abstract: Friction between silicon nitride (Si3N4) and bearing steel (GCr15) affects the hybrid bearing performance. The effects of graphene as an additive in n-hexadecane (C16H34) lubricating oil on the lubricating properties of a Si3N4-GCr15 friction pair were studied. The effects of pressure and shear velocity on the coefficient of friction and friction force were probed experimentally, while the changes in the van der Waals energy, shear stress, and thickness of the solid film in the lubrication area were simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…To demonstrate how the silver nanoparticles improve the adsorption of the fluid layer to the Fe layer, we calculated the energy by intercepting the final frame of shear conformation at 400 ps. 24,25 The equations below are used to calculate the binding energy and interaction energies ( E b i n d and E , respectively) of the fluid layer with the Fe layer 26,27 : where E F l u i d and E Fe represent the energies of the fluid layer and Fe layer, respectively. These values were obtained through single-point energy calculations.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate how the silver nanoparticles improve the adsorption of the fluid layer to the Fe layer, we calculated the energy by intercepting the final frame of shear conformation at 400 ps. 24,25 The equations below are used to calculate the binding energy and interaction energies ( E b i n d and E , respectively) of the fluid layer with the Fe layer 26,27 : where E F l u i d and E Fe represent the energies of the fluid layer and Fe layer, respectively. These values were obtained through single-point energy calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Tribological Characteristics [197] A clear investigation was concluded about the effect of sliding velocity and load capacity on the formation of the nano tribo-films at the contacted surfaces [198] Frictional heating and anti-wear properties of the friction pair is controlled through the existence of nanoparticles [199] Simulations of MD clarified that Gr nano additives could form a thick layer of tribo-film that can help in reducing the coefficient of friction and friction force [200] Nanofluids have a higher transition pressure than the base fluid, with an excellent load-carrying capacity [201] Theoretical guidance was implemented for the lubrication mechanism of MOS2 nanoparticles [193] Confirmation of the ball-bearing lubrication mechanism of nanoparticles under mild velocities and loads [189] The load-carrying capacity of nanofluid is improved regarding the base oil before the rupture of the lubricant film [120] Atomistic simulations confirmed the mending mechanism of nanolubricants through which nanoparticles fill in valleys of the sliding asperities Over and above that, artificial intelligence models can also predict the different behaviours of lubricant performance, regarding their tribological and other behaviours [202][203][204]. One of these tools is the artificial neural network (ANN), which is considered a widely accepted novel modelling approach [203].…”
Section: Referencementioning
confidence: 99%
“…To study a graphene additive film in n-hexadecane lubricating oil, Zhang et al performed pin-on-disk tests and molecular dynamic studies. It was found that the adsorption of the lubricant could be increased by adding graphene, and shear stresses on the surface were reduced [4]. Wu et al studied graphene oxide nanoplatelets as a lubricant additive for the contact of Si 3 N 4 ceramic/GCr15 steel in a four-ball tester.…”
Section: Introduction 1introduction To Dry Lubricationmentioning
confidence: 99%